ENGLISH-A CRITICAL REVIEW OF ISLAMIC TEACHINGS ON MENTAL HEALTH POLICIES AND PRACTICES FOR SCHOOL CHILDREN - Masood Ahmad; Muhammad Nasir Khan; Muhammad Asif Iqbal (دی اسکالر)
The study aims to critically review the Islamic teachings on mental health policies and practices for the psychological well-being of public sector secondary school students. The study is conducted through purposive sampling technique for the selection of school Principals and senior Islamic education educators serving in public sector secondary schools in Punjab. Unstructured interview is used as a main tool of research for this study. Findings: The study concludes Islamic teachings provide a clear picture to streamline the mental health policies and practices for school children and concrete policies and practices in Islamic perspectives are essential need for the psychological well-being of secondary school students in any country of the world. In general, findings of the study are applicable anywhere for school education department concerning the significance of policies and practices for the psychological well-being of secondary school students and can also be used to improve the strategies for training school Principals and educators.